Diversification of business and its implications for the welfare of traditional fishermen community in Uso Village, Batui District, Luwuk Banggai, Central Sulawesi Province - Srinurmahningsi, Sri; Andaki, Jardie A; Wantasen, Adnan (AQUATIC SCIENCE & MANAGEMENT, 2017)
Title (Bahasa Indonesia): Diversifikasi usaha dan implikasinya terhadap kesejahteraan masyarakat nelayan tradisional Desa Uso,Kecamatan Batui,Kabupaten Luwuk Banggai,Provinsi Sulawesi Tengah This study aims to determine the business diversification selected by the fishing community in maintaining family life, to determinethe difference in choice of business diversificationas well as the implications on the fishing communityof Uso Village, Batui District, Banggai Regency, Central SulawesiProvince. This study used a mixed method, which is a research approach that combines qualitative and quantitative research. Data used in this research is both descriptive and analytical. Comparative test was performed using Student’s t-test. The results of this study concluded that 1) there is diversification outside the fishing effort by the fishermen of the village,such asworking as construction workers, company workers, motorcycle taxi drivers, merchants and farming, 2) there is a significant difference between fishing effort and business diversifications in which the contsruction workers have lower income then the fishing efforts, while the income of business diversifications as company workers, motorcycle taxi drivers, and farmers are not significant, 3) diversification of fishing effort has a positive impact on the lives of fishermen to use their spare time not to fish due to weather factors, replace lost income because it does not go to the sea, and combines a variety of businesses in outside the fishing business potential in increasing the family income of fishermen in the village, and 4) cash-flow and financial analysis shows fishing effort is feasible, as well as diversification is feasible as the support of fishing effort.Penelitian ini bertujuanuntuk menentukan diversifikasi usaha yang dipilih oleh masyarakat nelayan dalam mempertahankan hidup keluarga,untukmenentukan perbedaan pilihan diversifikasi usaha danimplikasinyapada masyarakat nelayan Desa Uso,Kecamatan Batui,Kabupaten Banggai,Provinsi Sulawesi Tengah. Metode yang digunakan dalam penelitian ini, yaitu mixed-method.Analisis data menggunakandeskriptif analitik. Uji perbandingan menggunakan uji-t. Hasil penelitian dapat disimpulkan, 1) diversifikasi usaha, yangdilakukan selain usaha penangkapan ikan, yaitu bekerja sebagai buruh bangunan, buruh perusahaan, tukang ojek, pedagang dan bertani, 2) terdapat perbedaan nyata antara usaha penangkapan ikan dengan diversifikasi usahadi mana pendapatan sebagai buruh bangunan lebih rendah daripendapatan nelayan. Sedangkan diversifikasi usahasebagai buruh perusahaan, tukang ojek,dan bertani,tidak berbeda nyata, 3) diversifikasi usaha nelayan berimplikasi positif pada kehidupan nelayan dalam memanfaatkan waktu luangsaattidak melaut karena faktor cuaca, mengganti kehilangan pendapatan karena tidak melaut, dan mengkombinasikan berbagai usaha di luar usaha penangkapan ikan yang berpotensi pada peningkatan pendapatan keluarga nelayan, dan 4) Cash-flowdan analisis finansial menunjukkanbahwausaha perikanan tangkap layak dilaksanakan, demikian pula diversifikasi usaha sebagai penunjang usaha nelayan.